ANALYSIS OF WOMEN'S FOLLOWER’S RECEPTION IN THE YOGYAKARTA REGION ON THE TIKTOK @BASYASMAN00 ACCOUNT ABOUT RAMADHAN 1443 H EDITION OF DAKWAH CONTENT - Santa Lorita Simamora; Annisa Nurulia Candra Dewi (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2022)
This study aims to identify and describe the reception analysis of female followers in the Yogyakarta area on the TikTok account regarding the da'wah content of the Ramadhan 1443 H edition. Research method: reception analysis. Research results on eight da'wah content videos have different positions. Through the results of the reception analysis of the followers, it can be concluded that generally informants are in a dominant position. The position of the informant refers to Stuart Hall's reception theory and model which divides the audience's position in perceiving and giving opinions about a content into three, namely a dominant position, a negotiating position, and an oppositional position.